Personal Hygiene and Nutrition Impact on Academic Performance of Primary School-Aged in Urban and Rural Gorontalo - Safrudin Tolinggi; Herman Hatta; Moh. Rivandi Dengo (Buletin Penelitian Kesehatan, 2025)
Introduction: Cultural and socioeconomic factors affecting sanitation, hygiene, and academic performance in Gorontalo remain unexplored, necessitating further study to develop targeted interventions and foster collaboration among stakeholders. This research aims to analyze the relationship between nutrition, personal hygiene, and academic performance among primary school students in Gorontalo. Methods: An observational cross-sectional study was conducted in Gorontalo City and Gorontalo Regency in 2019, involving 456 children aged 8–11. Data were collected through questionnaires, interviews, weight (digital scales), and height measurements (microtoise). Statistical analysis was performed using chi-square and logistic regression techniques. Results: Results indicated no significant difference in personal hygiene between urban and rural students (p=0.805), but significant variation in nutritional status (p=0.006). Regression analysis showed a strong correlation between personal hygiene and academic performance (β=1.880, OR=6.556, p=0.002). These findings underscore personal hygiene as a critical factor for improving academic performance, particularly as outdoor play activities may compromise hygiene among primary school-aged children. Enhancing personal hygiene should therefore be prioritized to improve both health and education outcomes. Conclusion:  Although no major differences in hygiene were found, nutritional disparities highlight the need for interventions addressing access to nutrition and hygiene education. Recommendations include fostering collaboration between schools, families, and community stakeholders to address sanitation and hygiene issues comprehensively. Further research should investigate cultural and socioeconomic factors influencing the interplay between hygiene, nutrition, and academic outcomes, ensuring context-specific strategies are implemented to enhance children’s well-being and performance.